Specific Morpho functional Changes of the Lymphatic System in Patients Suffering from Burns (Eurasian Research Bulletin, 2022)
An Important role in the body's adaptation to adverse endo - and exogenous factors is played by the immune system (is), the importance of which in maintaining immune homeostasis and, consequently, the necessary level of adaptive potential of the body (APO), it is difficult to overestimate. This function is performed in the interaction of various immunocompetent organs, one of which is the lymph nodes (LU), visceral and peripheral (somatic) A new algorithm for studying the functional immunomorphology of lymph nodes is proposed, based on the determination of five parameters at the tissue level and the calculation of three coefficients. The new approach allows us to objectively and accurately assess the structural and functional state of organs both in normal and pathological conditions, which reflects the immune status and the overall level of adaptive potential of the body.